Empowering Young Indonesian Women: Reflections on the Role of a Puan Bisa Ambassador - Zahra, Dinda Amalia (Proceedings Series on Social Sciences & Humanities, 2025)
This reflective essay undertakes an in-depth examination of the transformative dimensions inherent in the role of a Puan Bisa Ambassador, the program designed to facilitate the empowerment of young Indonesian women. The program, orchestrated by Puan Bisa, strategically centers its objectives on the spheres of mental health, self-improvement, and career development. With a deliberate intent to dismantle entrenched societal barriers stemming from patriarchal cultural norms, economic constraints, and a deficiency of parental support for educational pursuits, the author meticulously elucidates their engagement in a structured training regimen comprising three distinct boot camps. These intensive sessions meticulously address pivotal subjects, including Mental Health, Self Improvement, and Career, culminating in the creation of substantive social media content crafted to exert a positive influence on its audience.